Land transport accidents: motorcycles as a public health problem - Ronaldo Semensato Maggent; Lutieri Mateus Benet; André Luis Machado Bueno (Revista Enfermagem Digital Cuidado e Promoção da Saúde, 2022)
Objective: To describe the epidemiological profile of hospitalizations for Land Transport Accidents, involving motorbikes, between the years 2011 to 2020, in the state of Rio Grande do Sul. Method: This is a descriptive epidemiological study with data from the Hospital Information System. Descriptive methods of analysis were used, with rates expressed in absolute numbers, relative frequency and weighted by population. Results: The results indicate that young white males concentrate the highest rates of hospitalizations in the state. They also suggest an increase of cases between the months of October and March, besides presenting the highest hospital mortality rates in the southern macro-region of the state. Conclusion: The knowledge of the profile of hospitalizations involved in these accidents can help in the structuring of strategies appropriate to local realities, with the aim of reducing accidents, damage to health, suffering and treatment costs.